Dielectric Properties of Oil Palm Mesocarp at Various Stages of Maturity - Zakaria, Zahariah (1998)
Dielectric properties at frequencies from 10⁻² to 10⁶ Hz and 0.2 to 20 GHz of mashed mesocarp of oil palm fruits at various stages of maturity are presented. The study includes the variation of dielectric constant, ɛ" and dielectric loss, ɛ" with moisture content ranging from 40 to 100% (wet basis). Measurement of the dielectric properties was done by using open-ended coaxial line probe and automated network analyzer for high frequency and spectrum analyzer for low frequency. The accuracy of the measurement is about 5% for dielectric constant, ɛ" and 3% for dielectric loss, ɛ". Results of measurements demonstrate a good relationship between dielectric properties of the mesocarp and moisture content or maturity of the fruit and also close to the values predicted by dielectric mixture models especially at frequencies above 3 GHz. At 10 GHz the difference between predicted and measured values are within 5%. Results of measurement also show that the ac ionic conductivity dominated in the region less than 3 GHz while above 3 GHz the dipole orientation of water molecules becomes dominant. Such a crossover in the form of dielectric loss from conductive loss to the dipole orientation about 2 GHz was observed. The effect of ac ionic conductivity is higher in young fruit and decreasing as a degree of maturity increases. Permittivity of oil palm mesocarp over the frequency range was found to increase with moisture content. A significant variation of ɛ' and ɛ" with maturity at 0.2 GHz and 10 GHz respectively make it suitable to form a maturity index as suggested by Nelson et al. With moisture content ranging from 25% to 85%, the ɛ' at 2 GHz varies from 11 to 61 and the ɛ" varies from 2.1 to 24.6 at 10 GHz. Based on the above values the permittivity-based maturity index for young and fully ripe fruits are 1 and 0.3 respectively.